Complex hyperbolic traveling wave solutions of Kuramoto-Sivashinsky equation using (1 ) G? ? expansion method for nonlinear dynamic theory - Yokuş, Asıf; Durur, Hülya (My University, 2019)
In this paper, it is (1 ) G? ?expansion method which are used to obtain new complexhyperbolic traveling wave solutions of the non-linear Kuramoto-Sivashinsky equation.Special values are given to the parameters in the solutions obtained and graphs aredrawn. These graphs are presented using special package program. This method isemployed to achieve the goals set for this study.
Keywords: Fizik; Uygulamalı; Matematik